"I have the strength to get through this using my past experiences with HIV": findings from a mixed-method survey of health outcomes, service accessibility, and psychosocial wellbeing among people living with HIV during the Covid-19 pandemic. Issue 7 (3rd July 2022) - Pantelic, Marija; Martin, Kevin; Fitzpatrick, Colin; Nixon, Eileen; Tweed, Marc; Spice, William; Jones, Martin; Darking, Mary; Whetham, Jennifer; Vera, Jaime H.
ABSTRACT: We examined the impact of Covid-19 restrictions on the wellbeing and access to care among people living with HIV (PLWH) in the UK. A cross-sectional anonymous online survey was circulated to PLWH attending care at three HIV services in Sussex. The questionnaire covered key themes: socio-demographic characteristics; changes in physical and mental health; accessibility of essential health services and information; and socio-economic concerns. Free-text qualitative responses were examined through framework analysis. Quantitative data from 653 respondents were available, with a subset of 385 free-text qualitative responses. In terms of mental health, 501 (77.6%) respondents reported feeling more anxious; 464 (71.8%) reported feeling more depressed than usual; and 128 (19.8%) reported having suicidal thoughts since the start of the pandemic. Respondents worried about running out of HIV medicine ( n  = 264, 40.7%); accessing HIV services ( n  = 246, 38.0%) as well as other health services ( n  = 408, 63.0%). Widespread resilience was also noted: 537 (83.3%) of respondents felt that living with HIV had equipped them with the strength to adapt to the Covid-19 pandemic. Findings highlight important gaps between the multifaceted needs of PLWH. Multisectoral collaborations and investments are needed to adequately support PLWH and to build resilience to future shocks within HIV services.